Studi Fenomenologi Konversi Keyakinan Seorang Pemuda Yahudi Ortodoks - Satria Adhitama (Universitas Kristen Maranatha, 2021)
Changes in beliefs are often referred to religious conversions. This study aims to describe and understand the religious conversion experience of a young man to become an Orthodox Jew. This study uses a qualitative approach with a phenomenological research strategy. The data analysis method used the Interpretative Phenomenological Analysis (IPA) method. The results of this study illustrate that the informant's belief in religious conversion is because he has Jewish blood and has been familiar with Judaism since childhood. The informant's parents gave him the freedom to choose what religion suits him. So that when the informant performs religious conversion, the informant does not experience significant obstacles. The obstacle is the requirements to become an Orthodox Jew which is quite complicated. Likewise, social relations are not too affected by religious conversion. Until now, the informant continues to internalize the teachings of his new religion. Keywords: conversion, IPA, Jews, phenomenological, religion